Scientific and Methodological Foundations for Studying the Problem of Using Modern Pedagogical Technologies in Education - Abdurashidovna, Dadajanova Dilbar; Khudayberdiyevna, Khudoyberdiyeva Zumrat (International Journal of Human Computing Studies, 2022)
This article is devoted to the scientific and methodological foundations for studying the problem of using modern pedagogical technologies in education system, the general features of pedagogical content technologies.